2013
DOI: 10.1155/2013/147514
|View full text |Cite
|
Sign up to set email alerts
|

The Exposure of Breast Cancer Cells to Fulvestrant and Tamoxifen Modulates Cell Migration Differently

Abstract: There is no doubt that there are increased benefits of hormonal therapy to breast cancer patients; however, current evidence suggests that estrogen receptor (ER) blockage using antiestrogens is associated with a small induction of invasiveness in vitro. The mechanism by which epithelial tumor cells escape from the primary tumor and colonize to a distant site is not entirely understood. This study investigates the effect of two selective antagonists of the ER, Fulvestrant (Fulv) and Tamoxifen (Tam), on the inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
2
9
1
Order By: Relevance
“…However, our findings add to the growing debate over the clinical benefits of these therapeutic drugs. In agreement with our study, Borley and co-workers recently showed that fulvestrant and tamoxifen promote an invasive phenotype in E-cadherin deficient MCF-7 cells by activating Src kinase [ 32 ] and others have found that these endocrine agents modulate cell invasion via distinct mechanisms [ 33 ]. Furthermore, tamoxifen treatment has been reported to induce the expression of matrix metalloproteinases (MMPs) [ 34 ], the well-known ECM-degrading enzymes that participate in tumour invasion [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, our findings add to the growing debate over the clinical benefits of these therapeutic drugs. In agreement with our study, Borley and co-workers recently showed that fulvestrant and tamoxifen promote an invasive phenotype in E-cadherin deficient MCF-7 cells by activating Src kinase [ 32 ] and others have found that these endocrine agents modulate cell invasion via distinct mechanisms [ 33 ]. Furthermore, tamoxifen treatment has been reported to induce the expression of matrix metalloproteinases (MMPs) [ 34 ], the well-known ECM-degrading enzymes that participate in tumour invasion [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Fulvestrant has been known to affect cell proliferation but has little to no effect on cell migration due to its ability to disrupt the dimerization process of the estrogen receptors. [71] The ability of irradiated gold-nanorod-bound assemblies to interact with actin filaments, which are crucial in cell invasion, supports our finding that the irradiated DDV2s were more successful at preventing cell invasion. Thus, gold-nanorod-bound FLS DDVs could play a pivotal role in reducing cell invasion and metastasis.…”
Section: Wwwbiotechnology-journalcomsupporting
confidence: 82%
“…[25] Furthermore, fulvestrant is hydrophobic and thus can bind efficiently to the assemblies and improve entrapment. [26,27] For DDV2, the self-assembled FLS nanoassemblies were first attached with gold-nanorods (10 nm in diameter) through cysteine-thiol chemistry in order to facilitate a photo-triggered drug release before encapsulating DDV2 with fulvestrant. Drug release, cytotoxicity, cell invasion studies, and impacts on actin cytoskeleton were examined before and after irradiation with 785 nm near-infrared laser for DDV2.…”
Section: Introductionmentioning
confidence: 99%
“…Tamoxifen is SERM acting on the β -estradiol estrogen receptors (ER) [ 14 , 15 ]. It has clinical therapeutic uses in human breast cancer treatment.…”
Section: Discussionmentioning
confidence: 99%